STRATEGI PENINGKATAN MUTU UNIVERSITAS: STUDI KASUS PADA UNIVERSITAS DHARMAWANGSA - Siregar, Muhammad Fuad Zaini; Iman, Mujhirul; Hidayat, Rahmat; Annisa, Vina (JURNAL TARBIYAH, 2024)
This research arises from the current low quality of education. Therefore, these studies are strategically focused on improving the quality of higher education institutions. The research method used is qualitative with a case study approach based at Dharmawangsa University. Data collection includes research planning, data collection, data analysis, interpretation and case development, case selection, report preparation, validation, and application of findings. The research findings show that at Dharmawangsa University, improving the university’s quality requires planning that emphasizes aspects such as the university's vision, mission, and goals articulated in the university's milestones, and determining the direction and policies of the university itself. Its implementation requires the establishment of Standard Operating Procedures, Terms of Reference, Budget Plans, and Activity Plans that prioritize the principles of participation, transparency, and accountability. In addition, both internal and external quality assurance of higher education is also very important, encompassing strategies, goals, quality standards, procedures, mechanisms, human resources, activities, information systems, and evaluations. The presence of the Quality Assurance Body is intended to support the creation of an effective internal control system within the university environment.